2020
DOI: 10.3390/jcm9010251
|View full text |Cite
|
Sign up to set email alerts
|

High On-Treatment Platelet Reactivity Affects the Extent of Ischemic Lesions in Stroke Patients Due to Large-Vessel Disease

Abstract: Background: Excessive platelet activation and aggregation plays an important role in the pathogenesis of ischemic stroke. Correlation between platelet reactivity and ischemic lesions in the brain shows contradictory results and there are not enough data about the potential role of stroke etiology and its relationships with chronic lesions. The aim of this study is to assess the relationship between platelet reactivity and the extent of ischemic lesions with the particular role of etiopathogenesis. Methods: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 36 publications
1
14
1
Order By: Relevance
“…Another novelty presented in this study is underlining the coexistence of aspirin resistance with the large-vessel disease etiology of cerebrovascular incidents and emphasizing the role of this etiology of stroke with a higher risk of recurrent events. In our previous study, we confirmed the role of large artery atherosclerosis for assessment of a significant relationship between platelet reactivity and the extent of brain ischemic lesions [6]. In this paper, we found that large-vessel disease is associated with high on-treatment platelet reactivity, and aspirin resistance and large vessel disease are independently associated with a higher rate of recurrent vascular events.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Another novelty presented in this study is underlining the coexistence of aspirin resistance with the large-vessel disease etiology of cerebrovascular incidents and emphasizing the role of this etiology of stroke with a higher risk of recurrent events. In our previous study, we confirmed the role of large artery atherosclerosis for assessment of a significant relationship between platelet reactivity and the extent of brain ischemic lesions [6]. In this paper, we found that large-vessel disease is associated with high on-treatment platelet reactivity, and aspirin resistance and large vessel disease are independently associated with a higher rate of recurrent vascular events.…”
Section: Discussionsupporting
confidence: 78%
“…Previous literature reports demonstrated that aspirin resistance in stroke patients is associated with negative traits, including poor clinical condition, poor early and late prognosis, new ischemic changes, larger extent of brain lesions in neuroimaging, or a higher risk of death or recurrent vascular events [6,7]. In assessing the recurrence aspect, the focus was not on the time of occurrence of the event and usually the short-term follow-up period was taken into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…One of the better-understood causes of cerebral ischemia is the pathology of large pre-cranial vessels, most often the internal carotid artery, which accounts for approximately 20-30% of all causes of stroke [6]. Our previous papers demonstrated the hyperaggregation and hyperactivation of platelets in this etiological subtype of ischemic stroke [7,8]. Furthermore, we hypothesize that it may be related to aspirin resistance and affect the clinical condition and prognosis due to the reduced inhibition of platelets.…”
Section: Introductionmentioning
confidence: 80%
“…In a subsequent publication in the same issue of the Journal of Clinical Medicine, Wisniewski et al assessed the relationship of platelet reactivity with early and late prognosis after an acute ischemic stroke, according to the stroke etiology [29]. Performing platelet function testing with two aggregometric methods in 69 individuals, they found higher platelet reactivity in patients with severe neurological deficits on day 90 after stroke onset, when compared to the group of patients experiencing mild neurological deficits [29].…”
Section: Novel Predictors Of Stroke Outcomementioning
confidence: 99%
“…In a subsequent publication in the same issue of the Journal of Clinical Medicine, Wisniewski et al assessed the relationship of platelet reactivity with early and late prognosis after an acute ischemic stroke, according to the stroke etiology [29]. Performing platelet function testing with two aggregometric methods in 69 individuals, they found higher platelet reactivity in patients with severe neurological deficits on day 90 after stroke onset, when compared to the group of patients experiencing mild neurological deficits [29]. In patients with acute ischemic stroke attributed to large vessel disease, a significant correlation between the platelet reactivity and functional status on the first day was also uncovered, with patients resistant to aspirin having a significantly greater possibility of severe neurological deficits on the first day of stroke compared to their aspirin-sensitive counterparts [29].…”
Section: Novel Predictors Of Stroke Outcomementioning
confidence: 99%